The Influence of Work Motivation and Principal Leadership on the Performance of Private High School Teachers in Medan Petisah District through Job Satisfaction as an Intervening Variable - Kennedy Utama; Kevin; Wiliam (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of work motivation and principal leadership on teacher performance through job satisfaction as an intervening variable among private senior high school teachers in Medan Petisah District, Indonesia. This study used a quantitative explanatory approach. The population consisted of 217 educators and education personnel from seven active private senior high schools, and 198 valid responses were obtained through questionnaire distribution. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the measurement model, structural model, direct effects, and indirect effects. The findings show that work motivation does not significantly affect job satisfaction, and principal leadership also does not significantly affect job satisfaction. However, job satisfaction has a positive and significant effect on teacher performance. Work motivation and principal leadership also have positive and significant direct effects on teacher performance. Principal leadership is the strongest predictor of teacher performance, followed by job satisfaction and work motivation. The indirect effects of work motivation and principal leadership on teacher performance through job satisfaction are not significant, indicating that job satisfaction does not mediate these relationships. The study concludes that teacher performance in private senior high schools is influenced more strongly by direct factors, particularly principal leadership, work motivation, and job satisfaction, rather than by an indirect mediation mechanism. This study is limited to private senior high schools in one district and uses cross-sectional self-reported data. This study contributes to educational management literature by showing that job satisfaction functions as a direct predictor of teacher performance, not as an intervening variable in this model.